2021
DOI: 10.13189/cea.2021.090402
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Optimal Hospital Design: A Comparative Study between Thai and Norwegian Public Hospitals

Abstract: This paper aims to determine the factors that influence the design process for public hospitals. The paper intends to provide knowledge regarding the hospital planning and design process from the perspective of policy makers, facilities managers, hospital planners and hospital designers. This study is a qualitative study, where twelve participants from Thai and Norwegian hospitals were interviewed. Respondents included hospital project directors (n=3), hospital planners/designers (n= 5), and facilities manager… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…Based on the study's findings, positive design recommendations have been formulated. From the medical staff interviews and focus group analysis, it was found that the result align with the literature that emphasises userfocused design (Prugsiganont and Waroonkun, 2021;Fronczek-Munter, 2016). Positive design can be delivered successfully when the involvement of designers and users is managed effectively (Fronczek-Munter, 2016).…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Based on the study's findings, positive design recommendations have been formulated. From the medical staff interviews and focus group analysis, it was found that the result align with the literature that emphasises userfocused design (Prugsiganont and Waroonkun, 2021;Fronczek-Munter, 2016). Positive design can be delivered successfully when the involvement of designers and users is managed effectively (Fronczek-Munter, 2016).…”
Section: Discussionsupporting
confidence: 64%
“…However, the approach should be used with consideration, which means the approach should not be used with inflated expectations. Furthermore, all involved parties (medical staff and hospital designers) should share the same understanding and expectations (Prugsiganont and Waroonkun, 2021). This "discussion" began by referencing the lack of user involvement in the three community hospitals, which resulted in several physical environment problems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it is important to consider the environmental health aspect in the hospital design to reduce the negative impact on the environment and the health of the patients and staff. The use of sustainable materials, water and energy conservation, and waste management practices should be incorporated into the HPD to promote a healthier and greener environment [19]. 9-Inadequate circulations in (HPD) can have contrary effects on the health and well-being of patients, staff, and visitors.…”
Section: Literature Reviewmentioning
confidence: 99%